The Importance of Empowering and Educating Girl Child in India - Meena, Khoda; Hazarika, Sangita (Integrated Journal for Research in Arts and Humanities, 2024)
This research paper aims to comprehend the value of girls' education in India for their empowerment. Indian society is witnessing a patriarchal society where all the important power is vested in the hands of the male. The problem of the study is that inadequate education for girls and women, results in low self-worth, uncertainty, and a lack of trust in the country's future and we cannot say the nation is developed until and unless the Girls are empowered. But regrettably, some obstacles prevent young girls from being empowered. In this paper, various legal provision for education is also highlighted. This research is purely based on qualitative research and data for research is based on secondary data viz., authentic government reports, websites, books, and journals. In this study, an attempt is made to point out gender discrimination, female education, and the reason dropout of girls from school. In light of this, it was determined that education may catalyze awareness, equity, and equality for women and girls in their revolutionary process of empowerment and the long-term sustainable development of a nation. The findings of the study are that as we compared all the states, not a single state witnessed a higher or equal literacy rate concerning girls, it is always lower than boys. The highest rate of girl dropout in India in I- IV Meghalaya has the highest rate of female dropouts with 60.6 then Jharkhand and Bihar with rates of 43.2 and 30.7 respectively. The study further suggests a few measures to ensure holistic female education to empower them including both the economic and societal development of women.